2019
DOI: 10.1080/14686996.2019.1578183
|View full text |Cite
|
Sign up to set email alerts
|

First-principles prediction of high oxygen-ion conductivity in trilanthanide gallates Ln3GaO6

Abstract: We systematically investigated trilanthanide gallates (Ln 3 GaO 6 ) with the space group Cmc 2 1 as oxygen-ion conductors using first-principles calculations. Six Ln 3 GaO 6 (Ln = Nd, Gd, Tb, Ho, Dy, or Er) are both energetically and dynamically stable among 15 Ln 3 GaO 6 compounds, which is consistent with previous experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…But still, a lot of studies are being conducted for the discovery of new families of oxide-ion conductors that may have sufficient ionic conductivity in intermediate- or lower-temperature range (300–700 °C). A recent report using first-principles calculations predicted that the Ln 3 GaO 6 (Ln = La, Nd, Gd, Tb, Ho, Dy, Er, or Lu) system might be a good oxide-ion-conducting system . However, earlier, a few experimental studies on some derivatives of these species have also been carried out by researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But still, a lot of studies are being conducted for the discovery of new families of oxide-ion conductors that may have sufficient ionic conductivity in intermediate- or lower-temperature range (300–700 °C). A recent report using first-principles calculations predicted that the Ln 3 GaO 6 (Ln = La, Nd, Gd, Tb, Ho, Dy, Er, or Lu) system might be a good oxide-ion-conducting system . However, earlier, a few experimental studies on some derivatives of these species have also been carried out by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report using first-principles calculations predicted that the Ln 3 GaO 6 (Ln = La, Nd, Gd, Tb, Ho, Dy, Er, or Lu) system might be a good oxide-ion-conducting system. 44 However, earlier, a few experimental studies on some derivatives of these species have also been carried out by researchers. Purohit et al had reported the Nd 3 GaO 6 -based system as a new family of oxideion conductor.…”
Section: ■ Introductionmentioning
confidence: 99%
“…E a was determined from the slope of the ln(D Li ) vs 1/T or ln(T•σ Li ) vs 1000/T plots. σ Li (T) at the dilute level can be calculated using the D Li (T) values and the Nernst− Einstein equation as follows (eq 4): 29,30…”
mentioning
confidence: 99%
“…SrTiO 3 has a lower oxygen vacancy migration energy of 0.5 eV (ref. 84 ) than the well-known LaGaO 3 (0.6 eV) 85 . Although, SrTiO 3 may have a higher conductivity, the oxygen ion transference number might not be optimum.…”
Section: Screening Of Stable Pure Perovskitesmentioning
confidence: 80%